Comprehensive Physiology 2001
DOI: 10.1002/cphy.cp070221
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ketogenesis in Liver

Abstract: The sections in this article are: Roles of Insulin and Glucagon in Substrate Supply for Hepatic Ketogenesis Effects of Ketones on the Endocrine Pancreas and Adipose Tissue Intrahepatic Partitioning of Fatty Acids Between Oxidation and Esterification Pancreatic Hormone Effects on Enzyme Substrate Availability Expression of Enzyme Activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…In ketosis, the blood pH remains buffered within normal limits [ 5 ]. Ketone bodies have effects on insulin and glucagon secretions that potentially contribute to the control of the rate of their own formation because of antilipolytic and lipolytic hormones, respectively [ 9 ]. Ketones also have a direct inhibitory effect on lipolysis in adipose tissue [ 10 ].…”
Section: Diabetic Ketoacidosis Vs Dietary Ketosismentioning
confidence: 99%
“…In ketosis, the blood pH remains buffered within normal limits [ 5 ]. Ketone bodies have effects on insulin and glucagon secretions that potentially contribute to the control of the rate of their own formation because of antilipolytic and lipolytic hormones, respectively [ 9 ]. Ketones also have a direct inhibitory effect on lipolysis in adipose tissue [ 10 ].…”
Section: Diabetic Ketoacidosis Vs Dietary Ketosismentioning
confidence: 99%
“…A second reason cited by the aforementioned authors that Arctic populations were not chronically in ketosis comes from a prevalent genetic variant of CPT1A known as the Arctic variant. The CPT1A enzyme is required for transporting fatty acids into liver mitochondria for oxidation and is thus on the critical path for hepatic ketogenesis (Zammit 2011). The variant, found in Arctic populations worldwide (Collins et al 2010, Gessner et al 2011, Clemente et al 2014, has been found to reduce CPT1A activity from 2-54% (average 22%) (Collins et al 2010).…”
Section: Evidence From Geneticsmentioning
confidence: 99%